Functional Genetic Variation in the 3′-UTRNTRK2 is Associated with Risk of Ischemic Stroke - Shi J; Sun Y; Hua J (Dove Medical Press, 2020)
Jiajia Shi,1,* Ying Sun,1,* Jiajia Hua2 1Department of Rehabilitation Medicine, Kunshan Rehabilitation Hospital, Suzhou, Jiangsu, People’s Republic of China; 2Department of Rehabilitation Medicine, The Sixth People’s Hospital of Nantong, Nantong, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiajia HuaThe Sixth People’s Hospital of Nantong, Nantong, Jiangsu, People’s Republic of ChinaTel +86-25-68137102Fax +86-513-80886666Email huajiajia1@yeah.netBackground: Stroke is a leading cause of death and disability worldwide. It remains difficult to treat brain injury and improve functional rehabilitation after cerebral ischemia. Brain-derived neurotrophic factor (BDNF) is involved in ischemic stroke (IS) through interactions in the CREB1-BDNF-NTRk2 pathway. In this study, we aimed to determine the association of NTRK2 gene polymorphisms and the effects of intergenetic interactions in the Chinese population.Materials and Methods: A total of 400 patients diagnosed with IS and 400 healthy controls were enrolled for genotyping. Detailed sequence-based analysis was predicted through bioinformatical investigation. Polymorphisms associated with miRNA were analyzed by a dual-luciferase reporter assay system.Results: Analysis of clinical characteristics revealed that IS was highly associated with exposure to cigarette smoking, alcohol intake, as well as metabolic diseases, such as diabetes, hypertension, and higher serum triglyceride concentration. Three polymorphisms in NTRK2 located in the 3ʹ-untranslated region (3ʹ-UTR) were genotyped. Logistic regression analysis showed that IS patients with rs11140793, rs7047042, and rs1221 polymorphisms had a higher risk of stroke and indicated a worse short-term recovery. The mRNA level of NTRK2 was suppressed in a mutant genotype compared with wild genotype. The suppression of NTRK2 was induced by the gain-of-binding ability of certain miRNAs through the direct binding of 3ʹ-UTR.Conclusion: Our research indicated that, by influencing the expression of NTRK2, the SNPs rs11140793, rs7047042, and rs1221 in the 3′UTR of NTRK2 can be used as risk factors for IS patients.Keywords: bioinformatics, NTRK2, ischemic stroke, homocysteine, miRNA